The Role of Emerging Trends in Education: The Role of Emerging Trends in Education - Mobo, Froilan (Future Science / FSH-PH Publications, 2021)
Emerging Technology Trends in Education is defined as those technologies that represent new and significant developments in the field like the Internet of Things (IoT), Education 4.0 which uses the Blending Learning, Augmented Reality, and Virtual Reality. In this time of Pandemic there are lots of challenges encountered like we cannot conduct a face to face classroom instruction and even the simulation of activities. Educational courses that require laboratory of simulation of activities is the biggest challenges because students are having hard time in understanding the practical real-time applications. In this time of Pandemic the evolution of Emerging Trends in Education helps a lot because it’s characteristics to adopt the requirements as required by the Inter-Agency Task Force on COVID-19 (IATF.)The purpose of the study is to help and strengthen the role of the Emerging Trends in our Education amidst the Pandemic and to help our Educational Sector boost up the level of education in the new Normal Approach and schools will be able to adapt these emerging technologies specially in this time of a pandemic. In conclusion Emerging Trends plays a vital role because majority of the educational sector are now using Augmented Reality (AR) and Virtual Reality (VR) in their practical laboratory exercises while at home.